Cerebral Ischemia Changed the Effect of Metabosensitive Muscle Afferents on Somatic Reflex Without Affecting Thalamic Activity - Pin-Barre, Caroline; Pellegrino, Christophe; Laurin, Frédéric; Laurin, Jérôme (Frontiers in Physiology, 2018)
The purpose of the present study was to examine the contribution of group III and IV metabosensitive afferents at spinal and supraspinal levels in rats subjected to middle cerebral artery occlusion (MCAO) with reperfusion during the acute phase. Animals were randomized in Control (n = 23), SHAM (n = 18), MCAO-D1 (n = 10), and MCAO-D7 (n = 20) groups. Rats performed the Electrical Von Frey and the Adhesive removal tests before the surgery and at day 1 (D1), D3, and D7 after MCAO. Animals were subjected to electrophysiological recordings including the responses of group III/IV metabosensitive afferents to combinations of chemical activators and the triceps brachii somatic reflex activity at D1 or D7. The response of ventral posterolateral (VPL) thalamic nuclei was also recorded after group III/IV afferent activation. Histological measurements were performed to assess the infarct size and to confirm the location of the recording electrodes into the VPL. Behavioral results indicated that MCAO induced disorders of both mechanical sensibility and motor coordination of paretic forepaw during 7 days. Moreover, injured animals exhibited an absence of somatic reflex inhibition from the group III/IV afferents at D1, without affecting the response of both these afferents and the VPL. Finally, the regulation of the central motor drive by group III/IV afferents was modified at spinal level during the acute phase of cerebral ischemia and it might contribute to the observed behavioral disturbances.